Study and Analysis on The Application of Cleaner Production in The Urea Fertilizer Industry (PT X) in Sumatera - Nurul Izzah Aulia; Nastiti Siswi Indrasti; Andes Ismayana (Andalasian International Journal of Applied Science, Engineering, and Technology)
Cleaner production is an environmental management strategy that is preventive, integrated and continuously applied to every process. The urea fertilizer industry certainly produces waste and allows for problems or constraints in the processing process. This study aims to obtain a cleaner production strategy to increase the efficiency of urea production. This research was studied at a urea factory in Sumatera with a high production capacity of 114,584 kg/hour. The cleaner production strategy was preventive maintenance for the CO2 compressor (B/C 1.91), cleaning demister on dust recovery prilling tower (B/C 3.62), making automatic door closer (B/C 84,54), addition wire mesh on air exhaust (B/C 91,96), add a condensate drop container overall (B/C 1,51) and make repairs to existing dehumidifier in bulk storage (B/C 30,94). Determining the priority of cleaner production alternatives using the MPE method results in the highest priority net production alternative being making automatic doors closer. If all alternatives are implemented, there will be savings in energy consumption of 2.052 kWh/tonne/day. Percentage of urea and NH3 loss can be reduced up to 20% so that the prilling unit production efficiency increased by 0.24% and the savings to be obtained range from 620 thousand - 45 billion rupiah/year.